2021
DOI: 10.1021/acs.analchem.1c03212
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Trace Sample Proteomics Unraveled the Protein Remodeling during Mesenchymal–Amoeboid Transition

Abstract: Deep mining the proteome of trace biological samples is critical for biomedical applications. However, it remains a challenge due to the loss of analytes caused by current sample preparation procedures. To address this, we recently developed a single-pot and miniaturized in-solution digestion (SMID) method for minute sample handling with three streamlined steps and completed within 3 h. The SMID approach outperformed the traditional workflow in substantially saving time, reducing sample loss, and exhibiting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…To decipher the key protein changes in cells during A2 cell transition, we developed an ultrasensitive trace sample proteomics based on liquid chromatography-tandem mass spectrometry (LC-MS/MS) and clearly unraveled the proteomic map. 23 We found a total of 632 differentially expressed proteins (DEPs) from the confined (Conf.) and nonconfined (Nonconf.)…”
Section: ■ Confinement Induces the Reduction Of Lamin A/c Expression ...mentioning
confidence: 99%
“…To decipher the key protein changes in cells during A2 cell transition, we developed an ultrasensitive trace sample proteomics based on liquid chromatography-tandem mass spectrometry (LC-MS/MS) and clearly unraveled the proteomic map. 23 We found a total of 632 differentially expressed proteins (DEPs) from the confined (Conf.) and nonconfined (Nonconf.)…”
Section: ■ Confinement Induces the Reduction Of Lamin A/c Expression ...mentioning
confidence: 99%
“…Further extending the time length, the identification number of protein groups decreased. Previous studies have reported that overnight protein digestion may result in ‘ trans -peptides’, a side reaction during digestion 11,26,27 When analyzing complex protein mixtures, the trans -peptide products from abundant proteins may interfere with the low-abundance protein peaks, resulting in a decreased identification number. Reducing the digestion time can avoid this side reaction for better proteomic profiling.…”
Section: Resultsmentioning
confidence: 99%
“…The false discovery rate (FDR) of peptides lower than 1% was used as the cut-off value for protein identification. 11,25…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid tube-to-tube transfer and related sample losses, it is critical to perform the multistep in a single pot. Thus, multiple methods have been described to minimize sample losses, such as in-StageTip digestion (iST), filter-aided sample preparation (FASP), and single-pot solid-phase-enhanced sample preparation (SP3) [ 127 , 128 ]. These methods have been used for the preparation of paucicellular samples, even a single cell.…”
Section: Potential Strategies In Kinase Spatial Assaymentioning
confidence: 99%